Microbiological Contamination of River Deltas in Similar Areas Worldwide With a Focus on the Pineios Delta in Greece - Marina Lampronikou; Konstantinos Kakavas (Air, Soil and Water Research)
The purpose of this paper is to compare various indicators of microbiological contamination in coastal areas near estuaries around the world. A major factor contributing to the presence of fecal coliforms is the geomorphology of the area, and, more particularly, whether the area concerned is an open or enclosed bay, the climate of the area, its tourism development, and, lastly, the urban, agricultural, livestock, or industrial activities carried out near river mouths. The aim was also to attempt to systematize the microbiological contamination of the above-mentioned estuaries around the world for broader applicability. Initially, four river estuaries from around the world (USA, Brazil, Spain, and Greece) were selected to be compared for the extent of their microbiological contamination. Ultimately, only the river mouths Jucar and Pineios in Spain and Greece respectively were comparable. Since it was not possible to compare the selected sites from all over the world using our own data and the literature, we limited ourselves to determining the microbiological contamination only in the region of Greece. A total of 128 water samples were taken throughout the year (32 water samples per season) from the four deferent sampling points. The only checkpoint in Greece that meets the requirements of Directive 2006/7/EC, for the desirable and maximum limits is Faros Stomio, spot-3. Enterococcus bacteria exceeded the maximum limit of 200 cfu/ml in May 2023 (600 cfu/ml) and February 2024 (426 cfu/ml) in Nea Messangala spot-1. The concentration of E. coli bacteria does not differ statistically from the desirable value of 250 cfu/ml before storm “Daniel” while it is statistically slightly lower than the desirable value of 250 cfu/ml after storm “Daniel” in Greece (before p  = .208 > .05 and after p  = .015 < .05 where .05 is the significance level).